That Fine Rain That Soaks You Through. Exploring the Role of Weather Lore, Cultural Identity, and Community Memory in Shaping Attitudes to Climate Change - Hall, Alexander (Frontiers in Climate, 2022)
As the limitations of climate change communication, which focusses on the dissemination of scientific knowledge has become apparent, climate studies scholars have called for richer, less reductive approaches. This includes adopting more emotive language, which is sensitive to the myriad ways communities understand and know their own environ and climate. While on the surface, the recent emotive turn of popular discourse on anthropogenic climate change seems to heed this call, the communication approaches most commonly associated with these developments are limited in their ability to reach diverse communities. This article attempts to address this gap and contribute to affecting action in a manner which is both proportionate with the immediate climate risk, but also successful in engaging a range of groups within the community. Exploring the links between weather lore, cultural identity, and memory in shaping individual perceptions of climate risks, the article asks how such identities, both at the community and individual level, might have informed indifference or inaction with regards to climate change. Adopting a style that situates the author within the narrative, this essay uses Manchester, England and its popular reputation as ‘the rainy city' to explore these themes. Charting the history of the popularization of the meteorological myth that Manchester receives excessive amounts of rainfall, the article exposes how this folklore is bound up in regional cultural identity and civic pride, first as “Cottonopolis” at the vanguard of the Industrial Revolution, and then in the city's post-industrial rebranding as a place known for music, comedy, and sporting successes. In drawing these threads through community, familial and individual narratives, the article concludes by outlining how we might better utilize affection and cultural identification with local environments and weather to promote future behavior change.